Interjurisdictional Information Sharing and National Security: A Constitutional and Legislative Analysis - Shore, Jacques; Crane, Brian; Wilson, John (McGill Law Journal / Revue de droit de McGill, 2016)
This article analyzes whether there are constitutional arguments that help or hinder the flow of information between the different levels of government in Canada. The duty to share information is acutely important to the protection of Canadian citizens and the maintenance of public order, responsibilities that often overlap the federal and provincial competencies. This article concludes that the Canadian constitution and its unwritten principles, such as co-operative federalism, demonstrate support for interjurisdictional information sharing. The true weakness in information sharing can largely be found in institutional and cultural impediments. It is critical for federal and provincial government agencies to work past these impediments to share information, thus fulfilling their obligations to protect the public and maintain order.